Potensi sektor ekonomi di kota samarinda - Soekapdjo, Soeharjoto (Faculty of Economics and Business Mulawarman University, 2019)
This study aims to determine the potential of economic sector at Samarinda city. Data used form 2013-2017 GRDP (constant prices at 2010), source from BPS. Using SLQ, DLQ analytical tools, Shift Share, and Klassen Typology. Results of this research is : progress in various sectors and economic potential shift at Samarinda city towards service sector, where Samarinda has slower potential development from East Kalimantan province. All sectors have a strong competitive potential, prospective, and the sector is in the advanced but depressed category, and there are 3 sectors that are relatively left behind. Samarinda city increasingly shows its identity as a metropolitan city.